DAMPAK HUKUM KEMBALINYA HAK EKONOMI KEPADA PENCIPTA PADA PERJANJIAN JUAL PUTUS ATAS LAGU DAN LIRIK - Budi Kurniawan (Paraguna, 2016)
Based on the articles number 18 and  122  of Copyright Act  No. 28, 2014, Sold  Flat  Contract will be  ended in  some  conditions.   Therefore   anyEcono mic   Rights   of  songwriter   and   arrangers  will   be  transferred automatically by music producers after  passing 25 ears plus 2 ears of contract, or in another case after waiting until passing to 25 years plus 2 ears if the contract  has  not come to an  end,  The legal effects with  theother parties especially between  music producers as copyright holders andthe third parties whose some Economic  Rights and  Mechanical   Rights being transferred are not simple.  The ending time of the contract by an Act is unusual since  it is a private area. It is also an unusual term to be applied in different effect from the  existing legal terms such  as Null and  Void, and Invalida te. This legal  research will find any  legal aspects caused  b thesearticles  application.  It will  also examine a preferred and suggested contractby government to transfer a copyright of license contract. In this case songwriters  and  arrange rs,  music producer or any other parties can  avoid  ancircumstances indicated as an act against law in the future.